Pengaruh Minat Belajar Matematika terhadap Kemampuan Pemahaman Matematis Siswa SMP - Tri Wulandari; Nita Hidayati; Attin Warmi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
This study aims to determine the effect of interest in learning mathematics to students' mathematical understanding abilities. This research is an ex-post facto research with an approach quantitative. The population in this study were all eighth grade students of SMP Negeri 1 Karawang Barat with 468 students using purposive sampling techniques so that the total sample was 38 students. Data collection techniques using test instruments, questionnaires and online (in the network). Data analysis techniques were performed using simple linear regression analysis. As a prerequisite for analysis, data normality test and data linearity test are performed. Data is processed using SPSS Software version 22 for windows. The results of this study indicate that there is influence interest in learning mathematics towards students' mathematical understanding abilities, this is indicated from the results of simple linear regression analysis that obtained the value of Sig. = 0.046 ???? = 0.05 so ????0 is rejected and ????1 is accepted or the regression model is linear with a coefficient of determination of 10.6%.